Perspectives on Maimonides : Philosophical and Historical Studies. - Kraemer, Joel L. (Littman Library of Jewish Civilization, The, 1991)
Moses Maimonides - philosopher, legalist, communal leader and physician - is considered the greatest intellectual figure of the Jewish world since the closing of the Talmud. This volume derives from a conference held at Tel Aviv University on Maimonides in Egypt.